PEMBUATAN KOMIK BERWARNA PADA MATERI ZAT DAN KARAKTERISTIKNYA UNTUK KELAS VII SMP/MTS - Anggreni, Tiara (journal of residu, 2019)
Comic is juxtaposed pictorial and other image in delibrate squence, intended to convey information and produce an aesthetic response in the viewer or reader. This reaserch aims to develope matter and characteristics colered comic for learning class VII SMP/MTs as learning media and to determine the validity and practicality level as media function. The type of this research is Research and Development (R&D) with 4-D models: (1) define, (2) design, (3) develop and (4) disseminate. This research is restricted until develop.The matter and characteristics colored comic was validated by two chemistry lecturers of FMIPA UNP and three sciense teachers of SMPN 4 Padang. The particality test was done by three sciense teachers of SMPN 4 Padang and 32 students of VII.2 class SMPN 4 Padang. This research used validity and practicality questionnaire as instrument. The coleccting data techniqe was conducted by distibuting the questionnaire and analyzed by Kappa Cohen formula. The result of analyzed show that matter and characteristics colored comic as learning media has 0,83  validity level and categorized as very high validity. The practicality level of this media has 0,87 categorized very high. The colored comic is very valid and practical to use as learnig media.